Responsible Innovation Ethics, Safety and Technology - Kormelink, Joost Groot (Open textbook library., 2019)
This textbook is based on the MOOC Responsible Innovation offered by the TU Delft. It provides a framework to reflect on the ethics and risks of new technologies. How can we make sure that innovations do justice to social and ethical values? How can we minimize (unknown)risks?The book explains: The concept and importance of responsible innovation for society Key ethical concepts and considerations to analyse the risks of new technologies Different types of innovation (e.g. radical, niche, incremental, frugal) Roadmap for Responsible Innovation by Industry The concept of Value Sensitive Design (VSD) It includes a link to all the web lectures as well as case studies ranging from care robots and nuclear energy to Artificial Intelligence and self-driving vehicles.